Melhoria de processos e informações via mapeamento de fluxo de valor: uma pesquisa-ação - (:unkn) unknown (Universidade Federal de Goiás, 2015)
Map administrative procedures is not an easy process, especially in public sectors where there is the need to meet the standards and procedures set out in laws and regulations. On the other hand, note that the Public Administration has invested in new practices that private companies has been used for long time for to improve services. One of these new practices widely used in manufacturing are the principles of Lean Production which aims to reduce and even eliminate waste that do not add value to the final product/service. In this context, the main objective of this research was to analyze the bidding process materials in the Regional Catalão, University Federal of Goiás with a focus on Value Stream Mapping tool of Lean Production and propose actions to increase their efficiency. The methodology used was action research, these strategies are to solve problems and / or to generate transformation. The results show that a benefit was obtained from the new procedures or actions such as training of personnel involved in the purchasing process 2012 to 2014 (considering the period from January to September each year), a reduction of about 16 % of cases returned for rectification; 5% for the canceled claims and 32.5% (from 40 to 27 days) in a request processing time in the external case. A simple estimate suggests that if all the actions proposed in this paper are applied one would expect a reduction of approximately 56.7% (from 231 to 99.25 days) in processing applications for processes carried out to bid and 56.8% (169 to 72.5 days) for processes performed by direct purchase (no bidding).
Improvement processes and information via value stream mapping: an action research
Keywords: Lean production; Mapeamento do fluxo de valor; Setor público; Lean production; Mapping value stream; Public sector; ADMINISTRACAO DE EMPRESAS::ADMINISTRACAO DE RECURSOS HUMANOS